First record of predation of Helicops leopardinus (Squamata: Dipsadidae) by a pitviper Bothrops gr. atrox (Squamata: Viperidae) in the Parnaíba River Delta, Piauí, Northeastern Brazil (Somma: Revista Científica do Instituto Federal do Piauí, 2026)
The genus Bothrops exhibits a generalist and opportunistic diet, with some records of ophiophagy. In this study, we describe the first record of predation of the water snake Helicops leopardinus by the pitviper Bothrops gr. atrox in the Parnaíba River Delta, Piauí, Brazil. A female Bothrops gr. atrox was collected on September 27, 2025, in a transition area between flooded sandbanks and sandy dunes, Ilha Grande municipality, Piauí. The stomachal content analysis revealed the presence of a water snake H. leopardinus, partially digested. This report expands knowledge about the diet of snakes of the B. atrox group, reinforcing their ecological plasticity and opportunistic behavior. It also suggests a greater chance of predation on aquatic species during their migration between bodies of water.